Quasi-static loads analysis of a 5-bladed rotor in maneuver using CFD/CSD coupling - Hong, S.; Jung, S.; Kim, K.; Park, S.H.; Lee, D.; Lee, J. (My University, 2019)
The airloads and structural loads of Light Civil Helicopter (LCH) rotor in a pull-up maneuver are investigated using a coupled approach between the computational structural dynamics (CSD) and computational fluid dynamics (CFD) methods. The LCH rotor characterized by 5-bladed system with elastomeric bearing and inter-bladed damper is modeled in the structural dynamics analysis. The periodic rotor solution along with its converged CFD/CSD delta airloads for steady level flight (? = 0.287) is used to perform the transient maneuver analysis. The resulting vehicle attitude angles and velocity profiles are then prescribed for the quasi-static maneuver analysis of the rotor. The predicted section airloads, vortex trajectories, angle of attack (AOA)distributions, and structural moments at specified instants and spatial locations are compared between transient CSD-alone predictions and quasi-static CFD/CSD maneuver results. It is demonstrated that CFD/CSD coupled results indicate more pronounced dynamic stall peaks and stronger 5 /rev oscillations on structural moments than those by the CSD-alone approach.